Acute graft rejection mimicking constrictive pericarditis after hearttransplantation. A case report - Burgos, Lucrecia María (2024)
Constrictive pericarditis (CP) is an infrequent complication following heart transplantation (HTx) and arises from diverse postoperative occurrences, including mediastinitis, pericardial effusion, or allograft rejection. Indeed, this rare clinical entity can be misdiagnosed as a rejection episode or restrictive cardiomyopathy. In this report, we present the case of a 43-year-old male who underwent HTx 1.5 years prior and was subsequently admitted to our center due to the gradual onset of symptoms indicative of right congestive heart failure, with an initial diagnosis of constrictive pericarditis.